Teaching the ABCs of bioinformatics: a brief introduction to the Applied Bioinformatics Course - Luo, J. (Briefings in bioinformatics, 2014)
With the development of the Internet and the growth of online resources, bioinformatics training for wet-lab biologists became necessary as a part of their education. This article describes a one-semester course 'Applied Bioinformatics Course' (ABC, http://abc.cbi.pku.edu.cn/) that the author has been teaching to biological graduate students at the Peking University and the Chinese Academy of Agricultural Sciences for the past 13 years. ABC is a hands-on practical course to teach students to use online bioinformatics resources to solve biological problems related to their ongoing research projects in molecular biology. With a brief introduction to the background of the course, detailed information about the teaching strategies of the course are outlined in the 'How to teach' section. The contents of the course are briefly described in the 'What to teach' section with some real examples. The author wishes to share his teaching experiences and the online teaching materials with colleagues working in bioinformatics education both in local and international universities.